Lucanthone Targets Lysosomes to Perturb Glioma Proliferation, Chemoresistance and Stemness, and Slows Tumor Growth In Vivo - Radin, Daniel P.; Smith, Gregory; Moushiaveshi, Victoria; Wolf, Alexandra; Bases, Robert; Tsirka, Stella E. (Frontiers in Oncology, 2022)
Glioblastoma is the most common and aggressive primary brain tumor in adults. Median survival time remains at 16-20 months despite multimodal treatment with surgical resection, radiation, temozolomide and tumor-treating fields therapy. After genotoxic stress glioma cells initiate cytoprotective autophagy, which contributes to treatment resistance, limiting the efficacy of these therapies and providing an avenue for glioma recurrence. Antagonism of autophagy steps has recently gained attention as it may enhance the efficacy of classical chemotherapies and newer immune-stimulating therapies. The modulation of autophagy in the clinic is limited by the low potency of common autophagy inhibitors and the inability of newer ones to cross the blood-brain barrier. Herein, we leverage lucanthone, an anti-schistosomal agent which crosses the blood-brain barrier and was recently reported to act as an autophagy inhibitor in breast cancer cells. Our studies show that lucanthone was toxic to glioma cells by inhibiting autophagy. It enhanced anti-glioma temozolomide (TMZ) efficacy at sub-cytotoxic concentrations, and suppressed the growth of stem-like glioma cells and temozolomide-resistant glioma stem cells. In vivo lucanthone slowed tumor growth: reduced numbers of Olig2+ glioma cells, normalized tumor vasculature, and reduced tumor hypoxia. We propose that lucanthone may serve to perturb a mechanism of temozolomide resistance and allow for successful treatment of TMZ-resistant glioblastoma.